Effects of Replanting and Retention of Mature Oil Palm Riparian Buffers on Ecosystem Functioning in Oil Palm Plantations - Woodham, Christopher R.; Aryawan, Anak Agung Ketut; Luke, Sarah H.; Manning, Paul; Caliman, Jean-Pierre; Naim, Mohd; Turner, Edgar C.; Slade, Eleanor M. (Frontiers in Forests and Global Change, 2019)
Oil palm plantations are a major agricultural land use in Southeast Asia. In the coming decades large areas of mature oil palm will be cleared and replanted. To inform more sustainable long-term production in this globally important crop, it is crucial we understand how replanting impacts ecosystem functions and services. We investigated whether several production-relevant ecosystems functions (dung removal, soil mesofauna feeding activity, herbivory, herbivore predation, and seed predation), and the simultaneous delivery of all functions (ecosystem multifunctionality), vary between recently-replanted oil palm (1-4 yr) and mature oil palm (23-30 yr) areas. Following new in-country and Roundtable on Sustainable Palm Oil (RSPO) guidelines, riparian buffers of mature oil palm, in which subsequent natural regrowth is allowed, are being preserved during the replanting cycle in plantations that lack natural forest reserves. We investigated whether or not mature oil palm riparian buffers maintain levels of ecosystem functioning beneficial for palm oil production. Only one function (herbivory) differed between mature and replanted areas, with higher levels of herbivory found in recently replanted oil palm. There was no difference in ecosystem multifunctionality between mature and recently-replanted oil palm. Mature oil palm riparian buffers were found to be valuable for maintaining lower levels of herbivory than recently-replanted oil palm. However, no other functions, nor ecosystem multifunctionality, differed between the mature oil palm riparian buffers and recently-replanted oil palm. The results of this study suggest that replanting has limited impacts on the ecosystem functions we considered. Furthermore, they suggest mature oil palm riparian buffers do not have negative impacts on production-relevant ecosystem functions in oil palm landscapes.